The effects of fast rise multiple lightning impulse on the electrical breakdown characteristics of MOV - Sin, Chock Tean (2006)
The behavior and performance of lightning protective devices such as metal oxide varistor under the application of multiple lightning impulses are different from the standard single stroke test. Since metal oxide varistor is the most common, economical and reliable device for low voltage and telecommunication systems lightning protection, a precise method of testing has to be adopted based on natural characteristics of lightning to accurately determine its performance and capability. In this work, laboratory studies are to be carried out on 1kV voltage and 250A current ratings metal oxide varistor (MOV). The test samples are to be subjected to multiple lightning impulses with fast rise time using the constructed Multiple Impulse Generator (MIGe). The electrical responses of the device such as resistance and breakdown voltage characteristics are then being analyzed to determine the effect on the varistors characteristics